Design, synthesis and physical evaluation of luminescent lanthanide-based supramolecular systems - Stomeo, Floriana (Trinity College (Dublin, Ireland). School of Chemistry, 2007)
This thesis entitled "Design, Synthesis and Physical Evaluation of Luminescent Lanthanide-based Supramolecular Systems" is divided into five chapters, and is in two parts. The first part. Chapter 2, deals with the synthesis and characterisation of naphthalimide-based and lanthanide-based luminescent pH sensors, for incorporation into hydrogels. The second part, Chapters 3 and 4, describes the design and the physical studies of chiral Eu III-based triple helicates, in partially aqueous and organic media.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin